Biliverdin reductase: a target for cancer therapy? - Gibbs, Peter E. M.; Miralem, Tihomir; Maines, Mahin D. (Frontiers in Pharmacology, 2015)
Biliverdin reductase (BVR) is a multifunctional protein that is the primary source of the potent antioxidant, bilirubin. BVR regulates activities/functions in the insulin/IGF-1/IRK/PI3K/MAPK pathways. Activation of certain kinases in these pathways is/are hallmark(s) of cancerous cells. The protein is a scaffold/bridge and intracellular transporter of kinases that regulate growth and proliferation of cells, including PKCs, ERK and Akt, and their targets including NF-κB, Elk1, HO-1 and iNOS. The scaffold and transport functions enable activated BVR to relocate from the cytosol to the nucleus or to the plasma membrane, depending on the activating stimulus. This enables the reductase to function in diverse signaling pathways. And, its expression at the transcript and protein levels are increased in human tumors and the infiltrating T-cells, monocytes and circulating lymphocytes, as well as the circulating and infiltrating macrophages. These functions suggest that the cytoprotective role of BVR may be permissive for cancer/tumor growth. In this review, we summarize the recent developments that define the pro-growth activities of BVR, particularly with respect to its input into the MAPK signaling pathway and present evidence that BVR-based peptides inhibit activation of protein kinases, including MEK, PKCδ and ERK as well as downstream targets including Elk1 and iNOS, and thus offers a credible novel approach to reduce cancer cell proliferation.